FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN LABA BERSIH PERUSAHAAN OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ruth Veny Martha; Benny Franco Sitompul (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This study aims to determine how much influence current ratio, debt to equity ratio, total asset turnover simultaneously on net profit margin on otomotive companies and component listed on The Indonesia Stock Exchange from 2013 to 2016. The data used are the current ratio, debt to equity ratio, total asset turnover and net profit margin’s company. Coeficient determination, F Value and T Test are using in this study. The result of this study is simultaneous effect of current ratio, debt to equity ratio, and total asset turnover have a significant impact on net profit margin.